PSYCHOLOGICAL ASPECTS OF THE DEVELOPMENT OF QUALITY EFFICIENCY OF THE EDUCATIONAL PROCESS (International journal of artificial intelligence, 2025)
Detailed the reforms in improving the quality of education. Deficiencies in the education system are also noted about the experience of the countries